Knockdown of NtCPS2 promotes plant growth and reduces drought tolerance in Nicotiana tabacum - Xu, Shixiao; Han, Wenlong; Cao, Kexin; Li, Bo; Zheng, Cong; Xie, Ke; Li, Wei; He, Lingxiao (Frontiers in Plant Science, 2022)
Drought stress is one of the primary environmental stress factors that gravely threaten crop growth, development, and yields. After drought stress, plants can regulate the content and proportion of various hormones to adjust their growth and development, and in some cases to minimize the adverse effects of drought stress. In our previous study, the tobacco cis-abienol synthesis gene (NtCPS2) was found to affect hormone synthesis in tobacco plants. Unfortunately, the role of NtCPS2 genes in the response to abiotic stress has not yet been investigated. Here, we present data supporting the role of NtCPS2 genes in drought stress and the possible underlying molecular mechanisms. NtCPS2 gene expression was induced by polyethylene glycol, high-temperature, and virus treatments. The results of subcellular localization showed that NtCPS2 was localized in the cell membrane. The NtCPS2-knockdown plants exhibited higher levels of gibberellin (GA) content and synthesis pathway genes expression but lower abscisic acid (ABA) content and synthesis pathway genes expression in response to drought stress. In addition, the transgenic tobacco lines showed higher leaf water loss and electrolyte loss, lower soluble protein and reactive oxygen species content (ROS), and lower antioxidant enzyme activity after drought treatment compared to wild type plants (WT). In summary, NtCPS2 positively regulates drought stress tolerance possibly by modulating the ratio of GA to ABA, which was confirmed by evidence of related phenotypic and physiological indicators. This study may provide evidence for the feedback regulation of hormone to abiotic and biotic stresses.